International Negotiations As Strategic Factors With Influence on the Configuration of the Social Policy in Romania - Stănescu, Simona Maria (Calitatea Vieții, 2014)
The negotiation process for Romania’s accession to the European Union (EU) has influenced the configuration of the social policy which was insufficiently prepared to fulfil the responsibilities of a Member-State. Despite the communist heritage in the field of social protection, the social neo-liberal measures adopted at the beginning of the 1990s were directed rather towards the contributory system (social insurances) and less towards the non-contributory system (social assistance), especially as rapid answer to the needs of the vulnerable groups. The standard negotiations with international investors (World Bank, EU, DfD) have influenced the social policy from Romania. The research hypothesis is that arguments in the field of social policy regarded as national priorities in various moments did not succeed in rendering flexible the eligibility criteria of international financings in the social field. The paper contributes to evaluating the national social policy as a step in supporting the elaboration of sustainable scenarios for socio-economic development.